Expanded scalp flap combined with laser hair removal to reconstruct facial defects around the hairline. Issue 9 (September 2022) - Liu, Shiqiang; Tang, Yinke; Ding, Jianke; Chu, Feifei; Yu, Zhou; Ma, Xianjie
Summary: Background: Congenital and acquired facial lesions around the hairline can bring huge physical and psychological trauma to patients. At present, reconstruction of this area remains a challenge. In this study, we present an alternative technique to reconstruct the aesthetic units using an expanded scalp flap combined with laser hair removal. Methods: We retrospectively reviewed 25 cases of facial lesions around the hairline reconstructed with this surgical technique between May 2014 and May 2020. Expander was implanted under the scalp as designed before the operation. After the expander was fully expanded, the lesion was removed and the scalp flap was transferred. Laser hair removal was performed on the transplanted skin flap 2 weeks after flap transfer. Results: There were ten cases of postburn scar, nine cases of congenital nevus, four cases of traumatic scar, one case of haemangioma, and one case of nevus sebaceous. The median times of laser treatment was 3 (range, 1–8). The median follow-up time was 11 months, ranging from 1 to 27 months. The colour and texture of expanded flaps were similar to adjacent tissue in all cases. The direction of reserved hair in transferred flaps was consistent with the direction of hair in the recipient area or contralateral hair. There were no complications, such as infection, blistering, discolouration, and ulceration. All patients were satisfied with the appearance of the reconstructed hairline and the surgical outcomes. Conclusions: The expanded scalp flap combined with laser hair removal is a feasible and effective technique to reconstruct both sides of the hairline simultaneously from a single donor site with a good colour match and a similar texture and thickness.